Análisis de las emisiones de dióxido de carbono (CO2) en Ecuador (1980-2010), mediante la Identidad de Kaya. - Gallegos Yaruquí, Jéssica Stefanía (2015)
In the present research the evolution of emissions of carbon dioxide (CO2) in Ecuador dioxide is analyzed from the viewpoint of the Kaya identity during the period 1980-2010. The methodology used is based on the Kaya identity in its simple and disaggregated form, likewise the Kaya identity - Porter, it is a derivation of the Kaya identity, analyzing GHG emissions from the agricultural sector, since according to the Ministry of Environment of Ecuador (MAE, 2011) this sector is the largest contributor to GHG emissions for the Ecuadorian case. With the results of the implementation of the Kaya identity in its simple and disaggregated form, it is considered that factors such as population, GDP per capita, energy intensity and carbonisation index contribute to increased climate change, also the factors that make up the Kaya identity - Porter as the carbon intensity of energy, GHG intensity of area, energy intensity and productivity, increase the problem of climate change from greenhouse gas emissions in the agricultural sector.